2020
DOI: 10.31557/apjcp.2020.21.6.1807
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Pilot Study of 20 Gy in 5 Fractions versus 27 Gy in 3 Fractions Radiotherapy for Treating Painful Bone Metastases: A Single Institution Experience

Abstract: Purpose: Radiotherapy is a very effective tool in the treatment of painful bone metastases. The aim of this study was to compare the palliative effect of radiotherapy between the standard fractionation schedule 20 Gy over 5 fractions (20Gy/5fr) and the high biological dose schedule 27 Gy over 3 fractions (27Gy/3fr) which is frequently used in Stereotactic body radio-surgery (SBRT). Methods: Patients were randomized to receive (20Gy/5fr)or (27Gy/3fr). The primary aim of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(43 citation statements)
references
References 9 publications
0
43
0
Order By: Relevance
“…Although the present study demonstrated the superiority of SBRT for pain palliation, randomized controlled trials comparing the pain-relieving effects between SBRT and cEBRT for bone metastases reported paradoxical results: superiority of SBRT over cEBRT [ 10 , 22 ] and non-superiority [ 23 , 24 , 25 , 26 , 27 ]. Consequently, the superior effectiveness of SBRT is still uncertain.…”
Section: Discussionmentioning
confidence: 51%
“…Although the present study demonstrated the superiority of SBRT for pain palliation, randomized controlled trials comparing the pain-relieving effects between SBRT and cEBRT for bone metastases reported paradoxical results: superiority of SBRT over cEBRT [ 10 , 22 ] and non-superiority [ 23 , 24 , 25 , 26 , 27 ]. Consequently, the superior effectiveness of SBRT is still uncertain.…”
Section: Discussionmentioning
confidence: 51%
“…of patients No. of patients with spinal metastases Minimum pain score for entry cEBRT dose (Gy/fx) SBRT dose (Gy/fx) SBRT dose (BED 10 , Gy) Dose gradient inside the PTV in SBRT Partial response definition Complete response definition Nguyen et al [ 15 ] 2019 Phase 2 160 0 2 30/10 12/1, 16/1 26.4, 41.6 PTV Dmax < 115% PD ICPRE criteria ICPRE criteria Berwouts et al [ 16 ] 2015 Phase 2 30 12 2 8/1 16/1 41.6 PTV Dmax ≤ 112.5% PD ICPRE criteria ICPRE criteria Ryu et al [ 10 ] 2019 Phase 3 353 353 5 8/1 16/1, 18/1 41.6, 50.4 No rules Improvement of ≥ 3 points without increasing the analgesic dose ICPRE criteria Sakr et al [ 17 ] 2020 Phase 2 22 Not available 4 20/5 27/3 51.3 Not available ICPRE criteria …”
Section: Resultsmentioning
confidence: 99%
“…Among the seven trials used for analysis in this study, four were assessed to have a low risk of bias, and one was assessed to have some concerns of bias (Additional file 2 ). Two trials were determined to have a high risk of bias owing to an undescribed randomisation procedure [ 17 ] and deviations from intended interventions [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among the published trials, 116 trials (52%) used PROs. PROs were primary end points in 45 trials 20,26,28,30,[34][35][36][37]42,48,53,[56][57][58][61][62][63]66,70,74,75,77,79,83,85,93,94,97,103,[108][109][110]113,115,117,118,124,125,127,128,130,133,134,137 (20% of all published trials; 31% of 145 trials clearly stating their primary end point; 39% of 116 trials including a PRO) and secondary end points in 71 trials 24,25,27,29,[31][32][33]…”
Section: Resultsmentioning
confidence: 99%
“…Median (IQR) sample size was 98 (41-230) patients in trials with a PRO as a primary end point, and 50 (31-132) patients in trials with a PRO as a secondary end point. Metastases and thoracic primaries were the most common treated sites (eFigure 3 in the Supplement ), including in 37 published trials 26 , 28 , 30 , 34 , 35 , 36 , 37 , 42 , 48 , 53 , 57 , 61 , 63 , 70 , 74 , 75 , 77 , 79 , 83 , 85 , 93 , 94 , 103 , 108 , 109 , 110 , 113 , 115 , 117 , 118 , 123 , 124 , 125 , 126 , 128 , 133 , 137 (82%) with a PRO as a primary end point and in 50 published trials 27 , 29 , 31 , 32 , 33 , 38 , 39 , 40 , 41 , 43 , 44 , 46 , 51 , 54 , 55 , 65 , 67 , 68 ,…”
Section: Resultsmentioning
confidence: 99%